Warm vegetarians? Heat waves and diet shifts in tadpoles. Issue 11 (November 2016) - Carreira, B. M.; Segurado, P.; Orizaola, G.; Gonçalves, N.; Pinto, V.; Laurila, A.; Rebelo, R.
Abstract: Temperature can play an important role in determining the feeding preferences of ectotherms. In light of the warmer temperatures arising with the current climatic changes, omnivorous ectotherms may perform diet shifts toward higher herbivory to optimize energetic intake. Such diet shifts may also occur during heat waves, which are projected to become more frequent, intense, and longer lasting in the future. Here, we investigated how heat waves of different duration affect feeding preferences in omnivorous anuran tadpoles and how these choices affect larval life history. In laboratory experiments, we fed tadpoles of three species on animal, plant, or mixed diet and exposed them to short heat waves (similar to the heat waves these species experience currently) or long heat waves (predicted to increase under climate change). We estimated the dietary choices of tadpoles fed on the mixed diet using stable isotopes and recorded tadpole survival and growth, larval period, and mass at metamorphosis. Tadpole feeding preferences were associated with their thermal background, with herbivory increasing with breeding temperature in nature. Patterns in survival, growth, and development generally support decreased efficiency of carnivorous diets and increased efficiency or higher relative quality of herbivorous diets at higher temperatures. All three species increased herbivory in at least one of the heat wave treatments, but the responses varied among species. Diet shifts toward higher herbivory were maladaptive in one species, but beneficial in the other two. Higher herbivory in omnivorous ectotherms under warmer temperatures may impact species differently and further contribute to changes in the structure and function of freshwater environments.